2020
DOI: 10.4103/picr.picr_181_18
|View full text |Cite
|
Sign up to set email alerts
|

An observational study on acute poisoning in a tertiary care hospital in West Bengal, India

Abstract: Aim: Poisoning is a preventable cause of morbidity and mortality in India. We undertook a prospective observational study to estimate the incidence, nature, severity and treatment outcome trends of acute poisoning in a tertiary care hospital in eastern India. Methods: All patients, admitted during the study period with acute poisoning, drug overdose and envenomation, were enrolled. Food poisonings, animal bites, chronic drug or chemical poisonings were excluded. Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
2
14
1
Order By: Relevance
“…Critically sick patients (9.5%) were transferred to the pediatric intensive care unit (PICU). However, no deaths were reported, similar to previous studies [4][5][6][7].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Critically sick patients (9.5%) were transferred to the pediatric intensive care unit (PICU). However, no deaths were reported, similar to previous studies [4][5][6][7].…”
Section: Discussionsupporting
confidence: 90%
“…Kerosene has been implicated as the most prevalent cause of accidental poisoning in the pediatric age group, as per studies conducted on children from various countries including India [5][6][7]. The major cause seems to be the incessant use of kerosene oil as fuel for cooking in rural and urban slum areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many congruent studies have also reported 0.3 to 0.6 % of emergency presentations due to poisons. 7,12,13 As in this study, most studies found maximum incidence of poisoning in age group less than 40 years and with men predominance, though, Ethiopia reports mixed results related to gender pre-Same model revealed that men have higher possibility for recovery and women are more prone to lethal outcome in acute chemical suicidal poisoning cases. Furthermore, it was also found that a randomly selected person has highest chances of cure if he/she is between 30-60 years of age and highest chances of death and LAMA if he/she is from the age group 60-75.…”
Section: Discussionmentioning
confidence: 45%
“…6 Though many studies regarding clinic-epidemiologic pattern of poisoning are available, only few of them explore the possible relationship between patient's basic characteristics, product used for poisoning and probable outcome. 7,8,9 Hence, this study was exclusively planned with following objective.…”
Section: Resultsmentioning
confidence: 99%